2006
DOI: 10.1007/s12020-006-0018-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of heterozygous carriers associated with compensated hypothyroidism in R450H, a common inactivating mutation of the thyrotropin receptor gene in Japanese

Abstract: Loss-of-function mutations in the thyrotropin receptor (TSHR) gene were described as a syndrome characterized by thyroid hyposensivity to biologically active TSH, ranging from euthyroid to severe hypothyroidism. In Japanese, a common mutation in the TSHR gene is R450H, which demonstrated moderately impaired receptor function. We studied six subjects of Japanese origin whose major abnormality was persistent hyperthyrotropinemia by genetic sequence analysis of the TSHR gene. Three subjects were homozygous for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…In the Japanese population, five different loss of function mutations (R450H, G498G, V473I, R519C, R519G) have been found [12, 17, 19, 20]. The R450H mutation affects the first cytoplasmic loop of the TSHR, and all patients with TSH resistance resulting from TSH receptor mutations identified in Japan possessed R450H mutation at least in one allele [12, 17, 19, 20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Japanese population, five different loss of function mutations (R450H, G498G, V473I, R519C, R519G) have been found [12, 17, 19, 20]. The R450H mutation affects the first cytoplasmic loop of the TSHR, and all patients with TSH resistance resulting from TSH receptor mutations identified in Japan possessed R450H mutation at least in one allele [12, 17, 19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…The R450H mutation affects the first cytoplasmic loop of the TSHR, and all patients with TSH resistance resulting from TSH receptor mutations identified in Japan possessed R450H mutation at least in one allele [12, 17, 19, 20]. In a previous study, COS-7 cells transfected with the R450H mutant demonstrated a 30–60% decrease in TSH binding activity and a 20–40% decrease in cAMP response to TSH, as well as expression in the cell surface as wild type [12].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, most molecular genetic researches on CH have been done in western countries, some have been carried out in Japanese population [6,28,29]. However,TSHR and TTF-1 genes mutations/variants have not been reported in Chinese population.…”
mentioning
confidence: 99%
“…The affected patients are commonly identified by routine laboratory tests and are asymptomatic. Most of the described cases are heterozygous for TSHR mutations, but biallelic mutations have been reported as well (Kanda et al, 2006;Russo et al, 2000;Sriphrapradang et al, 2011;Tenenbaum-Rakover et al, 2009;Tonacchera et al, 2001Tonacchera et al, , 2007.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…It was only in 1995 that the cause for RTSH syndrome in that case was shown to be a mutation in TSHR (Sunthornthepvarakul et al, 1995). Since the first report of CH caused by a TSHR mutation, several cases of loss-offunction mutations of TSHR have been reported: most are missense mutations, but deletions and insertions have been identified as well (see http: www.hgmd.cf.ac.uk/ac/ gene.php?gene=TSHR and OMIM#275200) (Abramowicz et al, 1997;Alberti et al, 2002;Biebermann et al, 1997Biebermann et al, , 2010Bretones et al, 2001;Camilot et al, 2005;Cangul et al, 2010;Clifton-Bligh et al, 1997;De Marco et al, 2009;de Roux et al, 1996;Fricke-Otto et al, 2005;Gagne et al, 1998;Grasberger et al, 2007;Jeziorowska et al, 2006;Jordan et al, 2003;Kanda et al, 2006;Nagashima et al, 2001;Narumi et al, 2009;Narumi et al, 2011;Park et al, 2004; …”
Section: Introductionmentioning
confidence: 99%